Socio-economic status of elderly population in rural areas of Haveri district in Karnataka: A geographical perspective - R.H. Nirmala; V.B. Saviramath (National Geographical Journal of India, 2025)
Rural areas, located outside urban centres, typically have a higher proportion of elderly residents, as younger populations tend to migrate to cities in search of better opportunities, leaving behind an aging demographic. This growing elderly population in rural regions often contributes to labour shortages and places additional strain on local economies. According to the India Ageing Report 2023, released by the United Nations Population Fund (UNFPA) and the International Institute for Population Sciences (IIPS), approximately 70 percent of the elderly population in India resides in rural areas. The country’s elderly population is projected to reach 158.7 million by 2025, with rural regions bearing the brunt of this demographic transition. In the Haveri district of Karnataka, the total projected elderly population is 1.6 lakh in 2024, with the rural elderly accounting for 115,019 individuals. The socio-economic status of elderly individuals in rural areas is defined by the interplay of social and economic factors that impact their quality of life, well-being, and access to opportunities. Rural elderly populations face several challenges, including inadequate healthcare services, poor housing and infrastructure, reliance on agriculture, weak transportation networks, limited access to nutritious food, and low literacy levels. This study aims to assess the well-being of the rural elderly in Haveri district by analysing their socio-economic conditions. Methodologically, the study adopts a spatio-temporal analysis of the rural elderly population, constructs a composite index to assess